Boosted interfacial charge transfer in SnO2/SnSe2 heterostructures: toward ultrasensitive room-temperature H2S detection. Issue 8 (19th February 2021) - Wang, Tingting; Wang, You; Sun, Quan; Zheng, Shengliang; Liu, Lizhao; Li, Jialu; Hao, Juanyuan
Abstract : Novel Sn atom cosharing SnO2 /SnSe2 heterostructures with a high-quality interface were synthesized via in situ thermal oxidation of SnSe. The boosted interfacial charge transfer endows the material with excellent H2 S sensing performance. Abstract : Constructing heterostructures could endow materials with exceptional properties in gas sensing applications owing to boosted interfacial charge transfer. The rational design and controllable synthesis of heterostructures with a high-quality interface, however, still remains a challenge. Herein, novel Sn atom cosharing SnO2 /SnSe2 heterostructures with an intimate-contact interface and tunable composition were fabricated via a facile in situ oxidation method. An efficient increase in charge transfer can be achieved at the heterointerface through density functional theory calculations. The gas sensor based on SnO2 /SnSe2 exhibited an ultrahigh response toward 10 ppm H2 S at room temperature (resistance ratio = 32), roughly 4.5 and 16 times higher than that of pure SnO2 and SnSe2, respectively. Moreover, the sensor exhibited an ultralow detection limit of 10 ppb, superior sensing selectivity, and reliable long-term stability. This enhancement is primarily attributed to the numerous n–n heterojunctions, the boosted interfacial charge transfer, and the increased active sites of SnO2 /SnSe2 heterostructures. The obtained results prove that SnO2 /SnSe2 is a promising candidate material for room-temperature H2 S gas sensing and offer guidance for rational material design to develop heterostructure-based sensors.